Childhood accidents--an endemic of epidemic proportion. Issue 3 (March 1981) - Sibert, J R; Maddocks, G B; Brown, B M
Abstract : Information about accidental injury to children was obtained by studying children who presented at hospitals in South Glamorgan during a 6-month period. Just under 10 000 children who lived in the area presented at hospital, which, if extrapolated means that 20% of children each year might be expected to attend hospital after an accident. The majority (71%) of children needed only simple investigation, treatment, or reassurance. The distance between the site of the accident and the hospital was directly related to the number of children presenting. The most common cause of injury was a fall, but dog bites also caused concern. Bicycle injuries were more common than police statistics indicate. We conclude that accident and emergency departments should give special attention to children.